2020
DOI: 10.1016/j.jcmgh.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Human Colon-on-a-Chip Enables Continuous In Vitro Analysis of Colon Mucus Layer Accumulation and Physiology

Abstract: An in vitro method is described for studying colonic mucus physiology by integrating primary human colonic epithelial cells in a microfluidic organ-on-a-chip device. The Colon Chip produces a mucus layer with thickness and bilayered microstructure similar to the human colon. CONCLUSIONS: This study shows the production of colonic mucus with a physiologically relevant bilayer structure in vitro, which can be analyzed in real time noninvasively. The Colon Chip may offer a new preclinical tool to analyze the role… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(160 citation statements)
references
References 51 publications
4
134
0
Order By: Relevance
“…Platforms should also provide access for on-demand sampling of secreted materials. The microfluidic Intestine-Chip seeded with enteroids from the small intestine [121][122][123][124] or colon 125 offers integrated manipulation of mechanical stretch, anaerobic compartmentalization, and endothelial interfacing. Silk scaffolding provides a highly permeable support network for enteroid monolayer communications with lamina propria.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Platforms should also provide access for on-demand sampling of secreted materials. The microfluidic Intestine-Chip seeded with enteroids from the small intestine [121][122][123][124] or colon 125 offers integrated manipulation of mechanical stretch, anaerobic compartmentalization, and endothelial interfacing. Silk scaffolding provides a highly permeable support network for enteroid monolayer communications with lamina propria.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Johansson et al 5 previously reported the necessity of bacterial colonization in vivo in mice to form a mucus bilayer. In contrast, Sontheimer-Phelps et al 2 have reported the establishment of an inner mucus layer sans bacterial interaction in their colon-on-a-chip in vitro model. Further investigations will likely shed light on these paradoxes and establish organ-on-a-chip microfluidic platforms as models for studying mucus production.…”
mentioning
confidence: 87%
“…Previously, the generation of a physiologically functional mucus bilayer in vitro had not been realized. Sontheimer-Phelps et al 2 have reported successful in vitro generation of a mucus bilayer using human organoid-derived colonic epithelial cells cultured using an organ-on-a-chip microfluidic device. They show that dynamic flow conditions result in a polarized, confluent colonic epithelial layer that maintained barrier function in vitro.…”
mentioning
confidence: 99%
“…In response to prostaglandin E2 the mucus layer underwent volume expansive. This model was responsive to prostaglandin in a Na-K-Cl cotransporter 1 dependent manner (Sontheimer-Phelps et al, 2020). There currently is not an organ chip model of the esophagus, although esophageal organoids have been developed from human pluripotent stem cells.…”
Section: Gut Chips Of the Different Regions Of The Intestinementioning
confidence: 99%